From ICF to laboratory astrophysics: ablative and classical Rayleigh–Taylor instability experiments in turbulent-like regimes. (18th December 2018) - Casner, A.; Mailliet, C.; Rigon, G.; Khan, S.F.; Martinez, D.; Albertazzi, B.; Michel, T.; Sano, T.; Sakawa, Y.; Tzeferacos, P.; Lamb, D.; Liberatore, S.; et al.
Abstract: Rayleigh–Taylor instability (RTI) occurs whenever fluids of different densities are accelerated against the density gradient, as is the case for the target ablator in ICF implosions. The advent of megajoule class lasers, like the National Ignition Facility (NIF) or Laser Mégajoule, offers novel opportunities to study turbulent mixing flows in high energy density plasmas for fundamental hydrodynamics or laboratory astrophysics experiments. Here, we review different RTI experiments, performed either at the ablation front or at a classical embedded interface. A two-dimensional bubble-merger, bubble-competition regime was evidenced for the first time at the ablation front in indirect-drive on the NIF thanks to an unprecedented long x-ray drive. Similarly, a novel large-area, planar platform enables the capabilities to perform long duration direct drive hydrodynamics experiments on NIF. Starting from imprinted seeds, a three-dimensional bubble-merger regime was also observed in direct-drive, as larger bubbles overtook and merged with smaller bubbles. In the astrophysical context, RTI also plays a role in supernova (SN) explosions, either of Type Ia or II. We report on experiments performed on the LULI2000 facility studying RTI in scaled laboratory conditions relevant for the physics of young SN remnants. Using a light CH foam as a deceleration medium, we measured, for the first time, the RTI mixing zone by PW transverse radiography.